FEM Analysis of High-Selectivity SAW Filter using SPUDT Structure - Tran, Manh Ha; Do, Quang Huy; Hoang, Si Hong; Nguyen, Thi Hue (Old Journal, 2017)
Wide-band surface acoustic wave (SAW) filters using single-phase unidirectional interdigital transducer (SPUDT) showed promise to achieve low loss and high selectivity. In this paper, the SAW filters were studied via finite element method (FEM) using 2D models and utilized YZ-LiNbO3 for piezoelectric substrate. With respect to the investigated center frequencies of 97 MHz and 179 MHz, the SPUDT SAW filter demonstrated low power losses (26.85 dB and 22.63 dB respectively) and high attenuation band (12.73 dB and 23.95 dB) in comparison to the bidirectional SAW filter. It was also identified that the changes in different electrode factors including the material, the thickness, and the quantity had influences on the SPUDT-type filter response.